2015
DOI: 10.1093/cvr/cvv226
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NAADP signalling on reperfusion protects the heart by preventing lethal calcium oscillations via two-pore channel 1 and opening of the mitochondrial permeability transition pore

Abstract: AimsIn the heart, a period of ischaemia followed by reperfusion evokes powerful cytosolic Ca2+ oscillations that can cause lethal cell injury. These signals represent attractive cardioprotective targets, but the underlying mechanisms of genesis are ill-defined. Here, we investigated the role of the second messenger nicotinic acid adenine dinucleotide phosphate (NAADP), which is known in several cell types to induce Ca2+ oscillations that initiate from acidic stores such as lysosomes, likely via two-pore channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 59 publications
4
49
0
Order By: Relevance
“…The results described in this paper provide clear structural evidence for nanojunctions between lysosomes and both the SR and mitochondria in rabbit ventricular myocytes; observations of the ultrastructural organisation which support the plausibility of earlier functional hypotheses23203543. Further, we have used Ned-19 and LysoTracker staining in live cells to localise NAADP-binding sites and showed that NAADP binding is restricted to acidic organelles in cardiac myocytes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results described in this paper provide clear structural evidence for nanojunctions between lysosomes and both the SR and mitochondria in rabbit ventricular myocytes; observations of the ultrastructural organisation which support the plausibility of earlier functional hypotheses23203543. Further, we have used Ned-19 and LysoTracker staining in live cells to localise NAADP-binding sites and showed that NAADP binding is restricted to acidic organelles in cardiac myocytes.…”
Section: Discussionsupporting
confidence: 84%
“…This information is important for constraining functional models of the calcium signalling roles of NAADP in the heart at rest and it is relevant to the contribution of NAADP signalling in the β-adrenergic response. Further, we investigated the proximity of lysosomes to mitochondria, in light of recent evidence supporting the role of NAADP signalling via TPC1 in ischaemia/reperfusion injury35.…”
mentioning
confidence: 99%
“…Decreased mitochondrial calcium levels inhibited the depolarization of the mitochondrial membrane and led to cardioprotection. Davidson and colleagues focused on calcium handling and secondary messenger NAADP, testing the hypothesis of cardioprotection using an NAADP antagonist Ned-K. Post ischemia-reperfusion they observed a cardiomyocyte protective mechanism by preventing the opening of the mitochondrial permeability transition pore [38]. …”
Section: Mitochondrial Transcription Factor a (Tfam)mentioning
confidence: 99%
“…A further development concerning the role of NAADP and TPCs during ischaemia and reperfusion is the observation that an antagonist of NAADP that is structurally related to Ned-19 (termed Ned-K) suppressed Ca 2+ oscillations in rat cardiomyocytes exposed to simulated ischaemia and reoxygenation (Davidson et al, 2015). Ned-K also reduced cell death under these conditions.…”
Section: Other Sites For Naadp Actionmentioning
confidence: 99%
“…In addition, in whole hearts subjected to ischaemia and reperfusion, Ned-19 reduced infarct size. Another important observation was that hearts from transgenic mice lacking TPC1 proteins also showed reduced reperfusion injury compared with WT controls (Davidson et al, 2015).…”
Section: Other Sites For Naadp Actionmentioning
confidence: 99%